Association between structural changes in brain with muscle function in sarcopenic older women: the women’s healthy ageing project (WHAP) - Hassan, Ebrahim Bani (J Musculoskelet Neuronal Interact, 2019)
OBJECTIVES: The involvement of changes in brain structure in the pathophysiology of muscle loss (sarcopenia) with aging remains unclear. In this study, we investigated the associations between brain structure and muscle strength in a group of older women. We hypothesized that structural changes in brain could correlate with functional changes observed in sarcopenic older women. METHODS: In 150 women (median age of 70 years) of the Women’s Healthy Ageing Project (WHAP) Study, brain grey (total and cortex) volumes were calculated using magnetic resonance imaging (MRI) analyses. Grip strength and timed up and go (TUG) were measured. The brain volumes were compared between sarcopenic vs. non-sarcopenic subjects and women with previous falls vs. those without. RESULTS: Based on handgrip strength and TUG results respectively, 27% and 15% of women were classified as sarcopenic; and only 5% were sarcopenic based on both criteria. At least one fall was experienced by 15% of participants. There was no difference in brain volumetric data between those with vs. without sarcopenia (p>0.24) or between women with falls (as a symptom of weakness or imbalance) vs. those without history of falls (p>0.25). CONCLUSIONS: Brain structure was not associated with functional changes or falls in this population of older women.